A Pilot Study of Vinorelbine Safety and Pharmacokinetics in Patients with Varying Degrees of Liver Dysfunction. (1st February 2019) - Gong, Jun; Cho, May; Gupta, Rohan; Synold, Timothy W.; Frankel, Paul; Ruel, Christopher; Fakih, Marwan; Chung, Vincent; Lim, Dean; Chao, Joseph
Abstract: Background: Vinorelbine has demonstrated anticancer activity and is primarily metabolized in the liver. This single‐institution, phase I pilot study describes the safety and pharmacokinetics of vinorelbine in patients with varying degrees of hepatic impairment. Materials and Methods: Patients with treatment‐refractory solid tumors were enrolled into treatment arms based on vinorelbine dose (weekly infusions of 7.5–30 mg/m 2 ) and liver function (normal liver function, mild, moderate, or severe liver dysfunction). Vinorelbine pharmacokinetics were evaluated to describe its relationship with liver function. Indocyanine green (ICG) clearance was assessed for correlation with pharmacokinetics. Results: Forty‐seven patients were enrolled, and a total of 108 grade 3–4 treatment‐related adverse events (AEs) occurred. Of these, grade 3–4 myelosuppression was the most common (34.3%). Thirty‐three (30.6%), 22 (20.4%), and 9 (8.3%) grade 3–4 AEs were observed in the vinorelbine 20 mg/m 2 /severe, 15 mg/m 2 /moderate, and 7.5 mg/m 2 /severe liver dysfunction groups, respectively, with the majority being nonhematologic toxicities. ICG clearance decreased as liver function worsened. Vinorelbine pharmacokinetics were not correlated with ICG elimination or the degree of liver dysfunction. Conclusion: For patients with severe liver dysfunction (bilirubin >3.0 mg/dL), vinorelbine doses ≥7.5 mg/m 2 are poorly tolerated. The high incidence of grade 3–4 AEs with 15 mg/m 2 vinorelbine in moderate liver dysfunction (bilirubin 1.5–3.0 mg/dL) raises concerns for its safety in this population. Vinorelbine pharmacokinetics are not affected by liver dysfunction; however, levels of the active metabolite 4‐O‐deacetylvinorelbine were not measured and may be higher in patients with liver dysfunction if its elimination is impacted by liver impairment to a greater degree than the parent drug. Abstract : Vinorelbine tartrate is a semi‐synthetic vinca alkaloid and an inhibitor of microtubule polymerization with demonstrated antitumor properties across a spectrum of cancers. The pharmacokinetics of vinorelbine may be altered in individuals with liver dysfunction, considering that hepatic metabolism serves as the predominant route of drug elimination. This article reports the pharmacokinetics and safety of vinorelbine in patients with varying degrees of hepatic impairment, including dosing recommendations in this population.